Keterampilan Memberi Penguatan dalam Pembelajaran di Kelas V SD - Hizbullah Hizbullah; Muchtar Muchtar; Putri Mahanani; Hizbullah Hizbullah; Muchtar Muchtar (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Abstract: The skill of giving reinforcement is one of the basic teaching skills that is very important to be mastered by the teacher. Reinforcement is any form of response that is part of the modification of the teacher's behavior on student behavior, which aims to provide information or feedback for students on the actions of the responses given. as an encouragement or correction. Strengthening skills provided by the teacher, students will feel compelled forever to respond whenever an activity appears from the teacher, or students will try to avoid responses that are considered useless. The purpose of this study was to determine the skills of teachers in providing verbal and non-verbal reinforcement in class V SDN Kotalama 2. This study used descriptive qualitative research. Data collection techniques in the form of observation, interviews, documentation, and instruments. The research subjects were classroom teachers, religion teachers, and fifth grade students at SDN Kotalama 2. The results showed that the skills to provide reinforcement in learning in grade V at SDN Kotalama 2 had been implemented well. The skill of giving reinforcement is carried out by the teacher in every learning that takes place. However, it was also found that several barriers to the skills of providing reinforcement from both classroom and religious teachers were found to be less than optimal. Abstrak: Keterampilan memberi penguatan merupakan salah satu keterampilan dasar mengajar yang sangat penting untuk dikuasai oleh guru, Penguatan adalah segala bentuk respon yang merupakan bagian dari modifikasi tingkah laku guru terhadap tingkah laku siswa, yang bertujuan untuk memberikan informasi atau umpan balik bagi siswa atas perbuatan responnya yang diberikan sebagai suatu dorongan atau koreksi. Keterampilan penguatan yang diberikan guru, maka siswa akan merasa terdorong selamanya untuk memberikan respon setiap kali muncul kegiatan dari guru, atau siswa akan berusaha menghindari respon yang dianggap tidak bermanfaat. Tujuan penelitian ini untuk mengetahui keterampilan guru dalam memberi penguatan verbal dan non-verbal dalam pembelajaran dikelas V SDN Kotalama 2. Penelitian ini menggunakan penelitian kualitatif deskriptif. Teknik pengumpulan data berupa observasi, wawancara, dokumentasi, dan instrument. Subjek penelitian adalah guru kelas, guru agama, dan siswa kelas V SDN Kotalama 2. Hasil menunjukan bahwa keterampilan memberi penguatan dalam pembelajaran di kelas V SDN Kotalama 2 sudah dilaksanakan dengan baik. Keterampilan memberi penguatan dilakukan oleh guru disetiap pembelajaran berlangsung. Namun, ditemukan juga beberapa hambatan terhadap keterampilan memberi penguatan baik dari guru kelas maupun guru agama yang kurang maksimal.